Analysis Of Exclusive Assessment Factors On Primipara Principal Mother - Asdinar; Irmawati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
ASI is an ideal source of nutrition with a balanced composition and adapted to the needs of the baby's growth. The purpose of this study is to analyze the factors of exclusive breastfeeding in primiparous postpartum mothers in the Gattareng health center work area. This research design uses an analytical design with a cross-sectional approach. The number of population and sample in this study is 30 respondents using total sampling. The data collection method used is a questionnaire sheet. From the results of the research, it was found that the characteristics of respondents were seen from the age of the majority of respondents aged 20-35 years as many as 28 respondents, and most of the respondents had an elementary education level of 11 respondents. % and the majority of respondents have a high cultural influence of 70.0% while for the most important health support some respondents have good health support at 76.7% and most respondents do not give Asi to their babies by 86.7% while bivariate analysis by using fisher's alternative chi-square statistical test. The results of the study showed that the level of knowledge (p = 0.008) and cultural influences (p = 0.005) had a significant relationship with breastfeeding exclusively while the support of health workers (p = 1,000) had no relationship with exclusive breastfeeding. So that this research can provide information about exclusive breastfeeding especially primiparous postpartum mothers and be input for health workers in the Gattareng health center and also useful for all parties and can be a reference for further research